2021
DOI: 10.1093/sleep/zsab072.862
|View full text |Cite
|
Sign up to set email alerts
|

722 Sleep Loss in Healthcare Workers During the COVID-19 Pandemic

Abstract: Introduction During the pandemic, healthcare workers have shared their stresses on social media, including regarding sleep disturbances. However, an assessment of sleep using validated measures among healthcare workers on social media is lacking. Methods A restricted, self-selection survey was distributed on Facebook, Twitter, and Instagram for 16 days targeting healthcare workers who were clinically active during COVID-19. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Healthcare workers (HCWs) are at risk for developing sleep problems compared to the general population due to their heavy workload and high-stress levels, which can be exacerbated during a pandemic or other health crisis. 1 4 A recent meta-analysis found that HCWs had a significantly higher prevalence of insomnia compared to non-HCWs throughout the pandemic. 5 Concerningly, compared to the initial months of the pandemic, HCWs’ sleep quality has progressively worsened and has been associated with psychiatric symptoms such as acute stress, depression, and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers (HCWs) are at risk for developing sleep problems compared to the general population due to their heavy workload and high-stress levels, which can be exacerbated during a pandemic or other health crisis. 1 4 A recent meta-analysis found that HCWs had a significantly higher prevalence of insomnia compared to non-HCWs throughout the pandemic. 5 Concerningly, compared to the initial months of the pandemic, HCWs’ sleep quality has progressively worsened and has been associated with psychiatric symptoms such as acute stress, depression, and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%